DEVELOPMENT OF SKILL TRAINING MODEL FOOTBALL BASIC TECHNIQUES THROUGH APPROACH GLOBAL ANALYTICAL GLOBAL - Aldo Naza Putra (Program Pascasarjana Universitas Negeri Jakarta, 2018)
This study aims to develop an exercise model of basic football technical skills through the Global Analytical Global approach for SSB PSTS students aged 11-12 years. Specifically, the objectives of this study are: To produce a design model of basic football engineering skills training through the Global Analytical Global approach for students aged 11-12 years. And see whether the model of training in basic football technical skills through the Global Analytical Global (GAG) approach is more effective in improving the basic technical skills of playing football for students aged 11-12 years. This research was conducted on soccer students of Padang Tabing PSTS Club aged 11-12 years. Development of a model of training in basic football technical skills through this Global Analytical Global approach uses the Research and Development (R & D) development model of Borg and Gall. Data collection was done by observation, questionnaire questionnaire to see the validation of the model tested in the field. Based on the results of data analysis that has been carried out, starting from the process of making the initial draft of the model, revision of the initial model, small group trials, large group trials, the researchers obtained very satisfying results, where football experts and trainers stated that this model had a purpose good for improving football playing skills. Variations in this model have good quality in improving playing skills. Variations in this model can enrich basic motion. Variations in this model are arranged based on the principle of practice from the easy to the difficult, and the variation of this model is very attractive for students aged 11-12 years. Keywords: Basic Football Technical Skills, Global Analytical Global